Pengaruh Promosi, Harga, dan Variasi Produk terhadap Keputusan Pembelian Konsumen pada Toko Retail Toserba Yogya Ketanggungan - Khana Amelia; Vivi Kumalasari Subroto (MANAJEMEN, 2026)
Increasingly tight retail competition requires business actors to design effective marketing strategies to influence consumer purchasing decisions. Therefore, this study aims to analyze the influence of promotion, price, and product variety on consumer purchasing decisions at the Yogya Ketanggungan Department Store. This study uses a quantitative approach with a survey method of 100 respondents selected using a purposive sampling technique, with data collection through a Likert scale questionnaire and analysis using multiple linear regression with the help of SPSS. The results of the study indicate that simultaneously promotion, price, and product variety have a significant effect on purchasing decisions with a coefficient of determination (R²) of 0.854, which means that 85.4% of the variation in purchasing decisions can be explained by these three variables. Partially, price and product variety are proven to have a significant effect on purchasing decisions, while promotions do not show a significant effect. These findings indicate that local retail consumers tend to be more sensitive to price factors and product variety than promotional activities, so the implication is that retail business actors need to focus more on strategies for competitive pricing and providing a complete product variety to increase consumer purchasing decisions.